Consumer perception about edible insects’ relation with environment and sustainability - Guiné, Raquel P. F. (2023)
The interest in adopting more sustainable diets can be a driver for consumers to engage the consumption of edible insects, even in countries where they are not culturally accepted as food. This work aimed to study the perceptions and knowledge of consumers in different countries towards edible insects and their relation with environment and sustainability. The present investigation was based on a questionnaire survey (11 questions) and this descriptive cross-sectional study was carried out on a non-probabilistic sample of 7221 participants from 14 countries. The participants in the survey revealed high knowledge (over 50%) about the sustainability issues related with edible insects as food. The sociodemographic variables education, sex and age are influential, by decreasing order of importance. Regarding living environment, rural areas have the lowest percentage of informed participants. Comparing countries, statistically significant differences were observed for all questions, making this the most important predictor for information about sustainability of edible insects. This is expected, having in mind that cultural influences are highly variable among the set of countries included in the study, with a high number of European countries, but also with Latin American countries like Mexico or Brazil, or Middle East countries like Turkey or Lebanon.